Impact of compensation on job satisfaction among healthcare workers: a systematic review - Hanis Abdul Rani; Nur Atiqah Mohd Ahwan; Faiz Daud; Aniza Ismail; Zaleha Md Isa (Universiti Kebangsaan Malaysia, 2025)
Job satisfaction among healthcare workers is crucial for workforce retention, organizational stability, and healthcare delivery. Compensation, including salary, incentives, and fringe benefits, is a key driver of job satisfaction. This systematic review examines the impact of compensation on the job satisfaction of healthcare workers, providing actionable insights for improving healthcare organizations. This systematic review followed PRISMA guidelines. A comprehensive search of PubMed, ProQuest, and Web of Science was conducted to identify studies published between 2015 and January 2024. Inclusion criteria focused on research examining the relationship between compensation and job satisfaction among healthcare workers. 12 studies met the inclusion criteria. Data were extracted, synthesized, and analyzed to identify themes related to compensation and job satisfaction. The review identified compensation as a key predictor of job satisfaction among healthcare workers. Despite its significance, widespread dissatisfaction and low satisfaction with compensation were reported across studies. Salary emerged as a critical factor, influencing satisfaction through its role in recognition of value and perceived equity. Incentives, particularly performance-based financing, demonstrated the potential to improve satisfaction by linking monetary rewards to performance metrics, although their effectiveness depended on robust organizational support. Fringe benefits, particularly opportunities for professional development, were found to enhance job satisfaction. Geographic and occupational differences were observed, with higher dissatisfaction in resource-limited settings and variations by location, nationality, and role. These findings highlight the multifaceted impact of compensation on satisfaction. Equitable compensation strategies must address salary, incentives, and fringe benefits. Regular evaluations, stakeholder engagement, and benchmarking against sector standards are essential steps to enhance job satisfaction, retention, and care quality across diverse healthcare settings.